A shower before bedtime may improve the sleep onset latency of youth soccer players - Whitworth-Turner, C.; Di Michele, R.; Muir, I.; Gregson, W.; Drust, B. (European Journal of Sport Science, 2017)
During the competitive season, soccer players are likely exposed to numerous factors that may disrupt the process of sleep. The current investigation looked to evaluate a practical sleep hygiene strategy (10-min showering at ~40°C before lights out), within a group of 11 youth soccer players in comparison to normal sleeping conditions (control). Each condition consisted of three days within a randomised crossover trial design. Sleep information was collected using a commercial wireless bedside sleep monitor. Measures of skin temperature were evaluated using iButton skin thermistors to establish both distal and proximal skin temperatures and distal to proximal gradient. The shower intervention elevated distal skin temperature by 1.1°C (95% CI: 0.1-2.1°C, p = .04) on average prior to lights out. The elevation in distal temperature was also present during the first 30-min following lights out (1.0°C, 95% CI: 0.4-1.6°C, p?<?.01). The distal to proximal gradient also showed a significant effect between the conditions within the first 30-min after lights out (0.7°C, 95% CI: 0.3-1.2°C, p < .01). On average the sleep latency of the youth soccer players was -7-min lower (95% CI: -13 to -2 min, p < .01) and sleep efficiency +2% higher (95% CI: 1-3%; p < .01) in the shower condition. These findings demonstrate that a warm shower performed before lights out may offer a practical strategy to promote thermoregulatory changes that may advance sleep onset latency and improve sleep efficiency in athletes.